Virtual Existence in Contemporary Serbian Novel - Gordić Petković, Vladislava (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
The paper sets out to explore the perspectives and strategies of virtual existence in contemporary Serbian novel in order to illustrate radical changes in the concept of reality and writers' concern with the fidelity to experience. A new surge of the so-called digital realism emerges simultaneously with the increase of awareness that the line between our digital selves and our real-world selves has become blurred and difficult to explain, while new technologies are required to go beyond what our human senses can encompass and deliver. The fictional realism of the digital age will also commit itself to young or middle-aged individuals that passionately attempt to define their aims and objectives so that they could fit into a newly constructed and acquired concept of reality. This is the case with the protagonists in the novels by Ivančica Đerić, Tamara Jecić and Aleksandar Ilić, all of them questioning both their offline and online identities. Their everyday life in a postmillennial world includes many intersecting empirical and virtual realities: love, career and sex take place in a dimension which ignores geography and physical distance and ultimately alters the concepts of time and space, as well the concepts of privacy and intimacy. The paper intends to examine the ways new digital technologies contribute to representations of reality in the novels of both accomplished and aspiring authors whose novels deal with ways of life amid social networks. The novels we analyzed show that the distinction between the virtual and the real world narrows, as the narratives range from intimate confession in letters and journals to tweets, notes and statuses, introducing verbal and structural experimental practices which involve shifting points of view.
Keywords: gender; narrative; social networks; virtual reality; Serbian novel